Heuristic for Enabling Lean Characteristics in Cellular Manufacturing using Reconfigurable Machines - Kant, Rajeev; L N Pattanaik; Pandey, Vijay (Asian Review of Mechanical Engineering, 2015)
Due to the rigidness of cellular manufacturing system (CMS), it lacks adaptability which is the ability to respond to changing products, product mix and production capacity, hence loosing competency in dynamic manufacturing environment. Reconfigurable machine tools (RMTs) are the great means to propel flexibility in CMS to enable a high degree of system responsiveness to frequent changes in cost effective way. In this paper, RMTs are used to exert lean characteristics in CMS by inheriting the desirable properties of RMTs. A heuristic is developed for embedding lean characteristics into machine cell design. The emphasis of this research is the formation of machine cells driven by specific product mix. An application example is included to illustrate the cellular model.